Development of linking methods of alcohols and thiols with vinyl azides for bio-application - Hayashi, Hirohito (Nanyang Technological University, 2020)
This thesis provides new strategies to introduce azido group into biological molecules through linking vinyl azides and 2-azidoacrylates onto alcohols and thiols. Furthermore, the azido linked products were used for further biological applications. The recent update and applications of vinyl azides in chemical synthesis were described in chapter 1 of the thesis. The unique reactivities of vinyl azides are introduced, such as vinyl azides as radical acceptors, nucleophiles and electrophiles. Chapter 2 of the thesis presented the new strategy to specifically introduce azido group onto the hydroxyl group. The linking started from an enamine-type nucleophilic attack of vinyl azides to F+ and Br+ followed by trapping the iminodiazonium ion using the primary or secondary hydroxyl group of the molecules including natural product derivatives such as sugars and steroids. The dyes were attached to the afforded azido linked testosterone product for bioimaging applications. Chapter 3 of the thesis describes the dual functionalization of cysteine containing peptide and protein through thiol-Michael addition of 2-azidoacrylates with sulfhydryl group. 2-azidoacrylates bearing the various functionalities such as fluorescent dyes were conjugated successfully with cysteine containing peptides and bovine serum albumin (BSA) to anchoring azido group in physiological conditions. The resulting conjugated peptides and BSA were used to perform a second functionalization through successive azide−alkyne cycloaddition to install another functionality. Therefore, dual functionalized peptides and BSA are obtained.